Distribusi Geografis Penyakit Parasit di Indonesia dan di Dunia - Reqgi First Trasia (Universitas Al Azhar Indonesia, 2021)
Parasitic disease is still a health problem in the world. However, some diseases caused by parasites are still being neglected, especially in tropical countries, so the World Health Organization (WHO) includes them in Neglected Tropical Diseases. Little is known and reviewed about the geographic distribution of parasitic diseases in the world, even though this condition is very important for the prevention of transmission. This article will review the geographic distribution of parasitic diseases in Indonesia. Several worms, protozoa, insects, and fungi are widely distributed cosmopolitan, especially in Indonesia which has a tropical climate. Child, Nutritional Knowledge, Consumption Pattern, Nutritional statusKeyword - Parasitic disease, Geographical distribution, Helminth infection, Fungal.